Efektivitas Program Revitalisasi Angkutan Perkotaan pada Trayek D10A Kota Depok - Vida Athalia; Mawar (PT Pustaka Cendekia Publisher, 2026)
Population growth and high commuter activity in Depok City, a buffer city for DKI Jakarta, have put serious pressure on the urban transportation system, characterized by the dominance of private vehicles and low public interest in conventional public transportation. In response to these problems, the Depok City Government, through the Transportation Agency, launched the Urban Transportation Revitalization Program in the form of the operation of Mikro Trans, one of which is on the D10A route from Depok Baru Terminal to Jatijajar Terminal. This study aims to analyze the effectiveness of the Urban Transportation Revitalization Program on the D10A route in improving the quality of public transportation services in Depok City. The research method used is descriptive with a qualitative approach. Data were collected through in-depth interviews, field observations, and documentation, with informants consisting of Transportation Agency officials, Mikro Trans drivers, and service users. Data analysis was carried out with reference to four indicators of program effectiveness according to Budiani, namely targeting accuracy, program socialization, goal achievement, and program monitoring. The results of the study indicate that the program has been on target and has been able to improve the comfort and safety of public transportation services, as reflected in the increasing number of passengers. Program socialization is considered quite effective but not yet inclusive, especially for groups less accessible to digital media. The goal of improving service quality is beginning to be achieved, although challenges remain with the cashless payment system and waiting times due to fleet limitations. Program monitoring is still suboptimal due to the limited number of drivers and customer complaint channels. Overall, the program is considered to have had a positive impact, but operational and monitoring aspects require strengthening to be more effective and sustainable.